Reversible Taste Loss in a COVID-19 Patient With Preexisting Chronic Smell Impairment. (February 2021) - Klein, Hadar; Karni, Noam; Israel, Sarah; Gross, Menachem; Muszkat, Mordechai; Niv, Masha Y.
Smell loss is important for coronavirus disease-2019 (COVID-19) screening and diagnosis. Particular attention should be paid to individuals with pre-COVID-19 chronic hyposmia or anosmia. We report a case of reversible taste impairment in a COVID-19 patient with chronically impaired sense of smell. This case emphasizes the importance of COVID-19-related taste assessment.